2022
DOI: 10.1111/acel.13748
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miR‐532‐5p induced by long‐term exercise rescues blood–brain barrier function in 5XFAD mice via downregulation of EPHA4

Abstract: The breakdown of the blood–brain barrier, which develops early in Alzheimer's disease (AD), contributes to cognitive impairment. Exercise not only reduces the risk factors for AD but also confers direct protection against cognitive decline. However, the exact molecular mechanisms remain elusive, particularly whether exercise can liberate the function of the blood–brain barrier. Here, we demonstrate that long‐term exercise promotes the clearance of brain amyloid‐β by improving the function of the blood–brain ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 47 publications
1
6
0
2
Order By: Relevance
“…Recent research indicates that mitochondrial‐enriched endothelial cell‐derived exosomes can restore TJ integrity by increasing ATP levels and restoring mitochondrial function 132 . In addition, exercise has been demonstrated to improve the BBB's structure and function by promoting the expression of TJ‐related proteins, inducing endothelial cell proliferation, and altering the types of miRNAs in exosomes in peripheral blood 133 …”
Section: Regulation Of Evs On Biological Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research indicates that mitochondrial‐enriched endothelial cell‐derived exosomes can restore TJ integrity by increasing ATP levels and restoring mitochondrial function 132 . In addition, exercise has been demonstrated to improve the BBB's structure and function by promoting the expression of TJ‐related proteins, inducing endothelial cell proliferation, and altering the types of miRNAs in exosomes in peripheral blood 133 …”
Section: Regulation Of Evs On Biological Barriersmentioning
confidence: 99%
“…132 In addition, exercise has been demonstrated to improve the BBB's structure and function by promoting the expression of TJ-related proteins, inducing endothelial cell proliferation, and altering the types of miRNAs in exosomes in peripheral blood. 133 In certain pathological conditions, EVs have been observed to potentially contribute to the breakdown of the BBB, and facilitate brain inflammation and tumor metastasis. [134][135][136] Research indicates that plasma-derived EVs from pediatric patients with OSA may impair the TJs of the BBB, resulting in increased permeability by disrupting ZO-1 continuity.…”
Section: Regulation Of Evs On Bbbsmentioning
confidence: 99%
“…The physical exercise-induced improvements in glymphatic function have been concentrated on the recovery of the aging-associated reduction of polarized AQP4 [ 32 ]. Nevertheless, the neuroprotective effects of physical exercise in dementia have also been associated with sleep regulation [ 134 ] and improvement of vascular function [ 98 , 135 ]. Aerobic exercise has been especially effective in reducing sleep medication intake and sleep latency in the elderly and patients with AD [ 134 ].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Since the prevalence of sleep disorders and physical inactivity among AD subjects is remarkably high [ 19 ], the beneficial effects of physical exercise on improving sleep could also contribute to the glymphatic function. Moreover, animal studies have shown that long-term physical exercise protects against neurovascular deterioration by preventing aging-associated astrocyte dysfunction, pericyte injury, and basal lamina impairments [ 98 , 135 ]. Of note, Morland and colleagues [ 136 ] demonstrated that the physical exercise angiogenic properties are dependent on the activation of the lactate receptor, hydroxycarboxylic acid receptor 1 (HCAR1), which is highly expressed in pericyte-like cells surrounding penetrating arterioles.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Other specific links between miRNAs and AD include miR-29c-3p, miR-193b, miR-132, miR-103, and miR-181c regulating Aβ activity; miR-181c, miR-31, miR-93 20 , and miR-146 21 modulating microglial inflammatory response in the CNS; as well as miR-125b 22 , miR-26b, miR-483-5p, and miR-502-3p influencing tau protein activity and NFT formation 23 . Additionally, miR-532-5p targets EPHA4 to ameliorate BBB damage 24 , while miR-126 targets EFHD2 to promote the formation and modulation of contextual fear memory in patients with AD 25 . The available data all point to the importance of miRNAs in influencing AD onset and symptoms.…”
Section: Introductionmentioning
confidence: 99%